Genetic structure and crude oil associated transcriptomic profile of environmental and clinical strains of pseudomonas aeruginosa (2018)
Historically, Pseudomonas aeruginosa research has been focused on its clinical importance as a common opportunistic nosocomial pathogen, even when its primary habitat must be the environment; few studies report the genetics, population dynamics or physiology of environmental strains. The lack of knowledge about P. aeruginosa behavior in the environment gives only a partial picture of its evolution since the bacteria changes its natural habitat. The general aim of this project is to contribute to the understanding of the genetic structure and population composition of Pseudomonas aeruginosa by producing new information given by strictly environmental isolates genomes and the transcriptomics of biofilms during crude oil biodegradation. In the first chapter, a revision of literature is presented to show and analyze the current model for Pseudomonas aeruginosa degradation of crude oil hydrocarbons. The second chapter addresses what genomic features of the "clinical group" and the "environmental group" are consistent amongst both groups or